If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-86=x-18
We move all terms to the left:
2x-86-(x-18)=0
We get rid of parentheses
2x-x+18-86=0
We add all the numbers together, and all the variables
x-68=0
We move all terms containing x to the left, all other terms to the right
x=68
| 4m^2+7m-36=0 | | –6+7q=6 | | –6+7q=6q | | 4(x-7)-2=-30 | | 60+.65x=3,390 | | 7x+24=19x+33 | | 4(x+7)-2=-30 | | 2x-5+4x-18=25 | | -7(x+5)=-5(x-3) | | -5t-14t=-19 | | 4(3x+1)−7x=6+5x−2 | | 16.2=20/n | | 7g-3g-1=11 | | 7k+15=120 | | 18+7w=-10-5+10w | | 5x +12=2 | | 3t+7t=36 | | e-4/15-e/10=1. | | 3n-6=-60 | | -3x-11+20=-22 | | 14v=-18+16v | | 19-13p=-17-7 | | 4(3x+8)=-17+25 | | x^2+5x=644 | | -5-19z=-15z+19 | | 4w+15=‐13 | | 5x-2x+5=7 | | 2x+17=8x-11 | | 6x+1=2x=5 | | 3(3g+2)=5(2g–1) | | e-4/15-e/10=1 | | -3=v+2 |